Biodiversity-Health-Sustainability Nexus in Socio-Ecological Production Landscapes and Seascapes (SEPLS) - Nishi, Maiko; Subramanian, Suneetha M.; Gupta, Himangana (Satoyama Initiative Thematic Review, 2022)
This is an open access book. It is a compilation of case studies that provide useful knowledge and lessons that derive from on-the-ground activities and contribute to policy recommendations, focusing on the interlinkages between biodiversity and multiple dimensions of health (e.g., physical, mental, and spiritual) in managing socio-ecological production landscapes and seascapes (SEPLS). This book provides insights on how SEPLS approaches can contribute to more sustainable management of natural resources, achieving global biodiversity and sustainable development goals, and good health for all. It is also expected to offer useful knowledge and information for an upcoming three-year thematic assessment of "the interlinkages among biodiversity, water, food, and health" (the so-called "nexus assessment") by the Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services (IPBES). The book begins with an introductory chapter followed by eleven case study chapters demonstrating the nexus between biodiversity, health, and sustainable development, and then a synthesis chapter clarifying the relevance of the case study findings to policy and academic discussions. It will be of interest to scholars, policymakers, and professionals in the field related to sustainable development.